PENGARUH KEPEMIMPINAN EFEKTIF KEPALA SEKOLAH DAN BUDAYA SEKOLAH TERHADAP KOMPETENSI GURU PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN (PJOK) SEKOLAH DASAR - Fatchurochman; Nurkolis; Ngasbun Egar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The research approach is ex post facto with an associative model using multiple regression analysis. The research was carried out at SD N in Batang Regency, totaling 446 schools. The population is 446 Public Elementary School PJOK teachers in Batang Regency. The sampling technique used Proportional Random Sampling and the sample size was calculated using the Slovin formula as many as 211 respondents. The data collection technique uses a questionnaire. Data analysis techniques test validity, reliability, normality, heteroscedasticity and hypothesis testing. Research results 1) The effective leadership of the school principal has an influence contribution of 42.5% on the competence of PJOK teachers in Batang Regency State Elementary Schools, while the remaining 57.5% is influenced by other variables, 2) School culture has an influence contribution of 51.3 % of the competency of PJOK teachers in Batang Regency State Elementary Schools, while the remaining 48.7% is influenced by other variables, 3). The principal's effective leadership and school culture together have an influential contribution of 59.1% to the competence of PJOK teachers in Batang Regency State Elementary Schools, while the remaining 40.9% is influenced by other variables. The conclusion is that there is an influence of the principal's effective leadership and school culture on the competence of physical education, sports and health (PJOK) teachers in Batang Regency State Elementary Schools. The suggestion in this research is that the effective leadership of the school principal together with school culture should be mobilized to become an instrument in improving teacher performance.